The impact of government expenditure on pro poor sectors in reducing poverty: The case of Kibaha District - Musiba, Crispin (Mzumbe University, 2024)
A thesis submitted in partial fulfillment of the requirement for award of the Degree of Master of Science in Economics (Msc. Eco) of Mzumbe University.